Approximate method for helical particle trajectory reconstruction in high energy physics experiments. (1st August 2022) - Topolnicki, K.; Bold, T.
Abstract: High energy physics experiments, in particular experiments at the LHC, require the reconstruction of charged particle trajectories. Methods of reconstructing such trajectories have been known for decades, yet the applications at High Luminosity LHC require this reconstruction to be fast enough to be suitable for online event filtering. A particle traversing the detector volume leaves signals in active detector elements from which the trajectory is reconstructed. If the detector is submerged in a uniform magnetic field that trajectory is approximately helical. Since a collision event results in the production of many particles, especially at high luminosities, the first phase of trajectory reconstruction is the formation of candidate trajectories composed of a small subset of detector measurements that are then subject of resource intensive precise track parameters estimation. In this paper, we suggest a new approach that could be used to perform this classification. The proposed procedure utilizes the z coordinate in the longitudinal direction in addition to the x, y coordinates in the plane perpendicular to the direction of the magnetic field. The suggested algorithm works equally well for helical trajectories with different proximities to the beamline which is beneficial when searching for products of particles with longer lifetimes.